Navigating Performance: Organisational Culture and Transformational Leadership in Yogyakarta Telesales - Katarina Wulandari; Norman Santoso; Silviana Halim; Abdul Rohman (Cakrawala Repositori IMWI)
This study examined how organisational culture and transformational leadership influenced telesales performance within a highly structured digital workplace, with a focus on the mediating role of job satisfaction. Although numerous studies have explored leadership and organisational culture in general contexts, limited research has investigated these factors within technology-mediated telesales sectors in emerging economies, where operations rely heavily on automated systems and strict performance metrics. This study hypothesised that organisational culture had a significant positive relationship with both job satisfaction and job performance, and that transformational leadership also had a significant positive relationship with both variables. Furthermore, it was hypothesised that job satisfaction had a significant positive relationship with job performance and mediated the relationships between organisational culture and job performance, as well as between transformational leadership and job performance. The researchers collected data through an online survey and analysed 143 valid responses using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that organisational culture had a strong positive effect on job satisfaction and job performance. Transformational leadership positively influenced job satisfaction; however, it unexpectedly demonstrated a significant direct negative effect on job performance, suggesting that its influence on operational performance occurred primarily through job satisfaction rather than through a direct pathway. Job satisfaction was found to be an important mediator in the relationship between organisational culture and transformational leadership with job performance. These findings provide valuable insights for telesales companies in developing economies, particularly by highlighting the importance of a supportive organisational culture and effective job satisfaction strategies in strengthening the contribution of leadership toward improved employee performance.